Immunomodulatory biomaterials in HIV-1 infection prevention, control and treatment - Li, Jiaying; Tang, Huan; Zhou, Xiaoyi; Ni, Zijun; Liang, Yuxin; Sun, Xinyue; Zhuang, Xun (Frontiers in Immunology, 2025)
Acquired Immunodeficiency Syndrome (AIDS), caused by the Human Immunodeficiency Virus (HIV), is a global infectious disease that remains a significant global health challenge. Although antiretroviral therapy (ART) has significantly reduced HIV-1-related morbidity and mortality, it cannot eradicate viral reservoirs latent in host cells and long-term use of ART is also associated with issues such as drug toxicity, drug resistance, and poor patient compliance. Recent achievements in biomaterials have provided new ideas and tools for AIDS prevention, diagnosis, and treatment. Therefore, this review aims to summarize the latest research progress on biomaterials for immune cell functional regulation and immune activation strategies in HIV-1 prevention, control, and treatment. These approaches include enhancing the functions of CD8+ T cells and macrophages and synergizing with the targeted delivery and immunomodulatory capabilities of biomaterials to achieve viral clearance and immune reconstitution. Current challenges and the great potentials of biomaterials in drug delivery, vaccine development, and physical barriers for HIV-1 infection are discussed, along with future perspectives. By systematically reviewing relevant research findings, this review may provide theoretical basis and technical tools for promoting the clinical translation and application of biomaterials for HIV-1 infection.